Pemikiran Ekonomi Abu Ubaid dan Relevansinya terhadap Ekonomi Modern - Vemi Fadila Sari; Titi Atifah Zahra Maha; Muhammad Ridwan; Randianto Alfandi (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
This study examines the economic thought of Abu Ubaid al-Qasim bin Sallam as presented in his seminal work Kitab al-Amwal, with a particular focus on public finance within the framework of Islamic economics. Abu Ubaid emphasized the importance of distributive justice and the balance between individual rights, society, and the state in managing public wealth. He outlined various fiscal instruments such as zakat, kharaj, jizyah, fa’i, ‘usyur, and khumus as sources of state revenue that must be administered in accordance with sharia principles. In addition, his views on agrarian policies (such as iqtha’, ihya al-mawat, and hima) and the function of money demonstrate a strong relevance to a just and sustainable modern economic system. This research employs a qualitative approach using literature review as its primary method. The findings reveal that Abu Ubaid’s economic concepts are not only contextually relevant to the Abbasid era but also remain applicable in addressing contemporary challenges in public finance and wealth distribution, particularly in strengthening zakat governance in Indonesia.